KETERAMPILAN SISWA MENULIS WACANA EKPOSISI MENGGUNAKAN TEKNIK OBSERVASI PADA KELAS XI SMK - Astuti, Ari Puji; ., Sukamto; Ramdani, Deden (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: The purpose of this study is the use of capital letters, punctuation, use of diction, and effective sentence by the students of class XI Administration 1 Semester 1, Muhammadiyah Vocational Schools of Pontianak Learning Year 2012/2013. This study used a descriptive method with qualitative form. The procedures in this study were learning. The technique used in this study is the observation techniques. Based on the results of data analysis can be summarized as follows. First, the average value of the ability of students to write essays of exposition in the use of capital letters is less well categorized, which is the percentage of 52 percent. Second, the ability of students to use punctuation well categorized, which is the percentage of 85,41 percent. Third, the ability of students to use diction categorized quite, which is the percentage of 65,97 percent. Fourth, the ability of students to use the phrase quite effectively categorized by percentage of 64.58 percent and the average value of students learning ability in written discourse exposition categorized simply by the value of 67.08. Indonesian teachers are expected to be more creative in presenting the subject matter. Key words: ability students, exposition, observation techniques. Â Abstrak: Tujuan penelitian ini adalah penggunaan huruf kapital, penggunaan tanda baca, penggunaan diksi, dan kalimat efektif oleh siswa kelasÂ XI Administrasi Perkantoran 1 Semester 1 SMK Muhammadiyah Pontianak Tahun Pembelajaran 2012/2013. Penelitian ini menggunakan metode deskriptif dengan bentuk kualitatif. Prosedur dalam penelitian ini adalah pembelajaran. Teknik yang digunakan dalam penelitian ini adalah teknik observasi. Berdasarkan hasil analisis data dapat disimpulkan sebagai berikut. Pertama, rataâ€“rata nilai kemampuan siswa menulis karangan eksposisi dalam menggunakan huruf kapital dikategorikan kurang baik, yaitu dengan persentase 52,08%. Kedua, kemampuan siswa menggunakan tanda baca dikategorikan baik, yaitu dengan persentase 85,41%. Ketiga, kemampuan siswa menggunakan diksi dikategorikan cukup, yaitu dengan persentase 65,97%. Keempat, kemampuan siswa menggunakan kalimat efektif dikategorikan cukup, yaitu dengan persentase 64,58% dan nilai rata-rata kemampuan belajar siswa dalam menulis wacana eksposisi dikategorikan cukup,yaitu dengan nilai 67,08. Diharapkan guru bahasa Indonesia agar lebih kreatif dalam menyajikan materi pelajaran. Kata kunci: kemampuan siswa, eksposisi, teknik observasi.